2000
DOI: 10.1073/pnas.180206197
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-triggered acrosomal exocytosis in human spermatozoa requires the coordinated activation of Rab3A and N -ethylmaleimide-sensitive factor

Abstract: The acrosome reaction of spermatozoa is a complex, calciumdependent, regulated exocytosis. Fusion at multiple sites between the outer acrosomal membrane and the cell membrane causes the release of the acrosomal contents and the loss of the membranes surrounding the acrosome. However, very little is known about the molecules that mediate and regulate this unique fusion process. Here, we show that N-ethylmaleimide-sensitive factor (NSF), a protein essential for most fusion events, is present in the acrosome of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 40 publications
7
68
1
Order By: Relevance
“…These data document that no individual Rab3 protein performs an isolated separate function that is required for reproduction or survival. For example, Rab3A or Rab3B KO mice exhibited no apparent decrease in weight or fertility, indicating that contrary to previous hypotheses, these proteins are not required for a fundamental gastrointestinal or reproductive function (Michaut et al, 2000). Most importantly, our data show that the four Rab3 proteins are functionally redundant, despite their differential distributions.…”
Section: Discussioncontrasting
confidence: 77%
“…These data document that no individual Rab3 protein performs an isolated separate function that is required for reproduction or survival. For example, Rab3A or Rab3B KO mice exhibited no apparent decrease in weight or fertility, indicating that contrary to previous hypotheses, these proteins are not required for a fundamental gastrointestinal or reproductive function (Michaut et al, 2000). Most importantly, our data show that the four Rab3 proteins are functionally redundant, despite their differential distributions.…”
Section: Discussioncontrasting
confidence: 77%
“…We previously reported that sperm contain a GEF activity that exchanges GDP for GTP on Rab3A when challenged with calcium or 8-pCPT-2′-O-Me-cAMP (35,47). We conducted those earlier experiments in SLO-permeabilized human sperm, but because we performed the Rab27 pull-down experiments reported in this paper with nonpermeabilized sperm, we wished to verify the Rab3A data under the same conditions.…”
Section: Resultsmentioning
confidence: 93%
“…4B). In the acrosomal proteins in spermatozoa, acrosin (19) and Nethylmaleimide-sensitive factor (NSF), which function in the acrosomal reaction (20,21), were rarely observed in the acrosome and head of sperm from Ht mice (Fig. S5 A-D).…”
Section: Resultsmentioning
confidence: 99%